2012
DOI: 10.1017/jfm.2012.378
|View full text |Cite
|
Sign up to set email alerts
|

Educing the source mechanism associated with downstream radiation in subsonic jets

Abstract: This work belongs to the ongoing debate surrounding the mechanism responsible for low-angle sound emission from subsonic jets. The flow, simulated by large eddy simulation (Bogey & Bailly, Comput. Fluids, vol. 35 (10), 2006a, pp. 1344-1358, is a Mach 0.9 jet with Reynolds number, based on the exit diameter, of 4 × 10 5 . A methodology is implemented to educe, explore and model the flow motions associated with low-angle sound radiation. The eduction procedure, which is based on frequency-wavenumber filtering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 75 publications
(86 reference statements)
1
38
0
Order By: Relevance
“…Thus, reduced-order (computationally efficient but approximate) models of the essential dynamics are invaluable for this effort in the near term. Recently, Kerhervé et al (2012) reported a strategy for reduced-order modelling of unforced jets to predict their noise signatures. The authors used far-field noise data to educe the acoustically important parts of the shear layer fluctuations, followed by a system identification approach to model their dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reduced-order (computationally efficient but approximate) models of the essential dynamics are invaluable for this effort in the near term. Recently, Kerhervé et al (2012) reported a strategy for reduced-order modelling of unforced jets to predict their noise signatures. The authors used far-field noise data to educe the acoustically important parts of the shear layer fluctuations, followed by a system identification approach to model their dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Following the observations of Mollo-Christensen (1963, 1967, a large body of experimental, theoretical and more recently numerical work has been dedicated to the eduction of wavepackets from turbulence (Crow & Champagne 1971;Lau, Fisher & Fuchs 1972;Hussain & Zaman 1981;Kerhervé et al 2012), to their study as a sound-generation mechanism (Michalke 1970;Crow 1972;Crighton 1975;Michalke & Fuchs 1975;Ffowcs-Williams & Kempton 1978;Crighton & Huerre 1990;Sandham, Morfey & Hu 2006;Cavalieri et al 2011aCavalieri et al , 2012bKerhervé et al 2012) and to their dynamic modelling (Michalke 1971;Liu 1974;Crighton & Gaster 1976;Tam & Morris 1980;Mankbadi & Liu 1984). Eduction methodologies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrodynamic waves have small amplitudes, no fixed phase reference, and their signature is therefore difficult to educe from the velocity field of unforced jets (a recent attempt has been made by Kerhervé et al 2012 using data from a large eddy simulation). The signature is, on the other hand, relatively clear in forced jets (Crow & Champagne 1971;Hussain & Zaman 1981;Cohen & Wygnanski 1987;Petersen & Samet 1988) and transitional flows, i.e.…”
Section: Introductionmentioning
confidence: 99%